Climate Change Strategy and Sustainable Power Technologies in China - Bin Li; Yoshiro Higano (European Regional Science Association (ERSA), 2005)
Global warming is likely to be the greatest environmental challenge among various known climate changes that related with many aspects of land use and water management in the 21st century. In general, the phenomenon of global warming is almost proportionally related with the pace of industrialization, which has to be resolved with high priority. Fossil fuel production and consumption is primarily responsible for the emission of greenhouse gases, especially carbon dioxide (CO2), into the environment, increasing the level of global warming. In this research, a policy mix as a kind of climate change strategy is proposed, imposing carbon tax in China. Based on available data, an eco-conscious socioeconomic framework model is built and several scenarios of energy use and CO2 emission are developed in order to evaluate comprehensively the effect of carbon tax on CO2 emission curtailment and introduce suitable alternative energy in China. Sustainable power technologies mean solar power technology and wind power technology in the research. The main target is to form a low carbon sustainable society in China, using a multi-sectoral macro-economical model including Input-Output (I-O) table. Then an optimum carbon tax rate is derived endogenously by running the simulation model under CO2 emission restrictions.
Keywords: 330